Modalitas Politik Eka-Richi Dalam Pemilihan Kepala Daerah Kabupaten Tanah Datar Tahun 2020 - Al Azhar; Akhyar Hanif; Mhd Alfahjri Sukri (UIN Mahmud Yunus Batusangkar, 2022)
The problem in this study is Eka Richi's Political Modalities in the 2020 Tanah Datar Regional Head Election. The purpose of this discussion is to find out what modalities Eka-Richi has in Winning the 2020 Tanah Datar Election and find out how Eka-Richi used these modalities to win the election. Tanah Datar Pilkada 2020. This descriptive qualitative research method is a research that reveals phenomena that occur in the field, namely about Eka Richi's Political Modalities in the 2020 Tanah Datar Regional Head Election. The results of the study found that: The first finding,┬áActivity/Experience is the community's support for the candidacy of the candidate pairs Eka Putra and Richi Apriadi through the 2020 Tanah Datar district election, cannot be separated from political capital that comes from the role of the candidate pair's organizational activities before advancing in the nomination. Second, Local Political Elite Support is a number of candidate strengths from local political elites from political organizations, social organizations and even political parties who can represent their interests. by finding votes/voter support for candidate pairs. Eka-Richi has relations or insiders both from outside the party or only as sympathizers such as collaborating with all lines of society, both young people and community leaders who are able to make a product that cannot be imitated by other candidate pairs, namely free plows. , one event one village. Second, the problem encountered is the black campaign or black campaign that attacks every segment owned by Eka-Richi. Eka-Richi built such a neat solution in preventing bad things from black campaigns by various parties.